An Article Review on Speeding Orthodontics (International Journal of Food and Nutritional Sciences, 2022)
The need for orthodontic care has increased significantly during the past few years. How to shorten orthodontic treatment is one of the most important questions since patients' main complaint about orthodontic treatment is that it takes too long and puts a lot of stress on them. Various procedures and strategies can be used to improve orthodontic tooth mobility. The evidence supporting the effectiveness of various techniques for accelerating orthodontic tooth movement was evaluated and presented in the current study.